Plasma and Serum Alpha-Synuclein as a Biomarker of Diagnosis in Patients With Parkinson's Disease - Chang, Chun-Wei; Yang, Shieh-Yueh; Yang, Che-Chuan; Chang, Chia-Wen; Wu, Yih-Ru (Frontiers in Neurology, 2020)
[Background] Parkinson’s disease (PD) is the second most common neurodegenerative disease, and α-synuclein plays a critical role in the pathogenesis of PD. Studies have revealed controversial results regarding the correlation between motor severity and α-synuclein levels in peripheral blood from patients with PD. [Objective] We examined α-synuclein levels in plasma or serum in patients with PD and investigated the relationship between plasma or serum α-synuclein level and motor symptom severity [Methods] We recruited 88 participants (48 patients with PD and 40 healthy controls). Clinical information was collected, and venous blood was drawn from each participant to be processed to obtain plasma or serum. The plasma or serum α-synuclein level was detected using monoclonal antibodies with magnetic nanoparticles, and was measured through immunomagnetic reduction. Plasma or serum α-synuclein levels were quantitatively detected. [Results] In patients with PD, the means of plasma and serum α-synuclein level were 3.60±2.53 pg/mL and 0.03±0.04 pg/mL, respectively. The areas under the receiver operating characteristic curve of plasma and serum α-synuclein for distinguishing patients with PD from healthy controls were 0.992 and 0.917, respectively. The serum α-synuclein level also showed a significant correlation with patients in H-Y stages 1-3 (r = 0.40, p = 0.025), implying that the serum α-synuclein level may be a potential marker of motor symptom severity in patients with early PD. [Conclusions] Our data suggest that the α-synuclein level in serum or plasma can differentiate between healthy controls and patients with PD. However, only serum α-synuclein levels correlated with motor severity in patients with early PD.